National Day at DeXi restaurant - Osadchuk, Daria (2021)
The main goal of the thesis is to introduce the Finnish food culture to XAMK international students. To achieve this goal, the following objectives were set: identify gastronomic events as an important issue in people’s food culture, develop a National Finnish Day event in the context of coronavirus pandemic, and demonstrate that the cooking video is a great way to present food culture to XAMK international students. The first part of the research provides theoretical data about the event organization, the types of online events that are relevant to conduct during the COVID-19 pandemic, information about the food culture of Finland and its iconic national dishes. The second part of the thesis is shown qualitative research that was used. There were conducted three interviews with representers of XAMK, who participated in the event organization at the university earlier. Based on the results of the interview, a menu was formed from the traditional Finnish dishes as Karelian pasties, Finnish salmon soup, and Finnish blueberry pie. The third part of the research is focused on video planning and implementation. Shooting and editing videos is a creative and enthralling process, although very time-consuming and meticulous. Quantitative research was used in the research as a survey. The survey was aimed at evaluating the first impression of the video “Let’s cook with Daria”, collecting the feedbacks. The results of the survey showed that the video was made successfully, it reveals the topic of the food culture in Finland. All of the respondents enjoyed watching the video, highlighted the well-chosen Finnish dishes, the ease, and usefulness of the information provided. In conclusion, the research shows how much the Finnish people appreciate and are proud of their food culture, dedicating holidays to the national Finnish dishes. For future videos, it is recommended to add voice comments, and cooking tips to the video. To increase the video quality, it would be great to have special shooting equipment to make a video from different angles.